Sport psychiatry in the Asia-Pacific: Contributions, trends, and future directions - Mohd Amiruddin Mohd Kassim; Assis Kamu; Nicholas Tze Ping Pang; Chong Mun Ho (APA PsycNet, 2025)
, Introduction: Sport psychiatry research in the Asia-Pacific region has gained momentum in recent years. This study aims to provide a comprehensive overview of sport psychiatry research in the Asia-Pacific, highlighting its evolution, thematic trends, and collaborative networks. Methods: Bibliometric analysis approach was applied to explore the research landscape of sport psychiatry in the Asia-Pacific region. Utilizing the Scopus database, a systematic search strategy was applied to retrieve English-language journal articles published between 1994 and 2024, focusing on affiliations from Asia-Pacific countries such as Australia, China, Japan, and others. The study analyzed annual scientific production, authorship patterns, institutional contributions, country-level collaborations, and thematic trends. Results and Discussion: Australia is the leading contributor and a dominant hub for global collaborations, followed by the United States and the United Kingdom. Keyword co-occurrence analysis highlighted recurring themes such as mental health, depression, exercise, and athlete performance, while thematic evolution analysis demonstrated a shift from central topics like sports medicine to contemporary concerns such as anxiety and outcome assessment. Collaboration networks, most-cited documents, and centrality metrics were identified to elucidate influential researchers, institutions, and research areas. Conclusion: This study provides a comprehensive overview of sport psychiatry research, offering insights into trends, collaboration patterns, and future research directions to advance athlete mental health and performance outcomes.